COMPORTAMIENTO POBLACIONAL DE MYZUS PERSICAE (SULZER) (HEMIPTERA: APHIDIDAE) SOBRE TRES HOSPEDEROS HORTICOLAS - Kahan, Andrea. E.; Bayo, María D.; Ricci, Elisabet M. (Acta Entomológica Chilena, 2022)
The main vital statistics of Myzus persicae (Sulzer) on three horticultura! species: Gallega lettuce, Ditmarch cabagge and Oliver Brussels sprout, were obtained. Aphids were reared under laboratory conditions at 20 ± 1°C, 14:10 hours of photoperiod and a relative humidity of 60-70%. Two cohorts were used per each horticultural species. Daily record of change of stage, number of dead individuáis and births was kept once adult stage was reached. Net reproductive rate (R0) appeared 4,2 times higher in Brussels sprout Oliver variety than in Galician lettuce and 1,3 times higher than in cabbage Ditmarch var. Intrinsic growth rate (rm) was significantly different among the three horticultural species. The aphid showed a higher capacity of survival and reproduction on crucifer than lettuce.